3D geometrically nonlinear augmented finite element method for arbitrary cracking in composite laminates. (15th October 2020) - Wang, Liang; Yang, Q.D.
Highlights: Large-deformation formulation of 3D A-FEM for multiple crack evolution in composites. Nonlinear element augmentation procedure for element stiffness and residual. Seamless coupling of intra- and inter-laminar cracks with geometric nonlinearity. Demonstrated analysis capability for coupled damage evolution in composite. Abstract: This paper, for the first time in literature, formulated and validated a three-dimensional, nonlinear augmented finite element method (3D A-FEM) that can account for multiple crack evolution in laminated composites under large deformation. The 3D A-FEM accounts for all major cracking events (intra-ply matrix cracking, fiber rupture/kinking, and inter-ply delamination) with explicit cohesive cracks. The computational scheme is achieved by coupling the 3D A-FEs for intra-ply cracks with 3D cohesive interface elements for inter-ply delamination. The strong discontinuities of both intra- and inter-ply cracks are explicitly represented by the geometrically nonlinear cohesive zone models (CZMs). The numerical capability is demonstrated by several benchmark tests with both in-plane and out-of-plane loadings. Results show that the A-FEM predicted progressive damage processes, including the arbitrary initiation of multiple cracks and their nonlinearly coupled progression with delamination all the way up to the final catastrophic failure, are all in good agreement with experimental results.